Stopping fast waves with a left-handed metamaterial slab - K. L. Tsakmakidis; Klaedtke, A.; Aryal, D.P.; Hess, O. (Optics InfoBase Conference Papers, 2006)
We show that, with judicious choice of opto-geometrical parameters, oscillatory waves guided by generalized left-handed slab waveguides can attain zero group velocity. Advantages compared to previous methods of slowing or stopping light are concisely discussed. © 2006 Optical Society of America.
cited By 0